A Review of the Fossil Record of Ecuador, with Insights about Its Challenges and Future Development (2018)
Here we present a review of paleontology in Ecuador for the last three centuries, including the most significant studies, localities and their fossil record. This review is focused on four major fields of paleontology, which are: vertebrate paleontology, invertebrate paleontology, paleobotany and micropaleontology-palynology. The main fossil discoveries for each of these fields are ordered chronologically by date of publication and summarized in tables, maps and figures. Finally, we briefly discuss the current and near future challenges of paleontological research in the country. © 2018 Asociacion Paleontologica Argentina. All rights reserved.